ChatGPT dan Ancaman terhadap Kemampuan Berpikir Kritis Mahasiswa : AWK Foucault pada Podcast GCED Isola Edu ChatGPT: Ini Respon Terbaik Dunia Pendidikan - Nurul Hidayah; Laksono Hafid Firmansyah; Firstly Yusuf Ar Ridho Rochman; A.A.I Prihandari Satvikadewi (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to analyze how ChatGPT has an impact on the way students and students think critically in the academic field. This article examines this topic based on descriptive qualitative research techniques with the perspective of critical discourse analysis, Foucault's model of knowledge and power. The media used as material for analysis in this research is excerpts from the GCED ISOLAedu podcast with the podcast title